Visit the website 123iitjee.manishverma.site for latest posts, courses, admission & more.

### Solve for $\left\{ {x,y,z} \right\}$, $x+xy+xyz=12$ $y+yz+xyz=21$ $z+xz+xyz=30$

It may be possible to isolate x, y, z in terms of xyz (say t) as follows:

$x(1+y+yz)=12$ [From the 1st equation]

Let us find y+yz in terms of t from the 2nd equation.

$y+yz=21-xyz=21-t$

Now, this y+yz can be substituted in the 1st step above.

$x(1+21-t)=12$

$\therefore x = \frac{{12}}{{22 - t}}$

Also, $y(1+z+xz)=21$ [From the 2nd equation]

$z+xz=30-t$ [From the 3rd equation]

So, $y(1+30-t)=21$

$\therefore y = \frac{{21}}{{31 - t}}$

Putting these values of x and y in the 1st equation $x+xy+t=12$ or $x(1+y)+t=12$,

$\left( {\frac{{12}}{{22 - t}}} \right)\left( {1 + \frac{{21}}{{31 - t}}} \right) + t = 12$

$\Rightarrow \left( {\frac{{12}}{{22 - t}}} \right)\left( {\frac{{52 - t}}{{31 - t}}} \right) + t = 12$

$\Rightarrow 12(52 - t) + t(22 - t)(31 - t) = 12(22 - t)(31 - t)$

$\Rightarrow 624 - 12t + 682t - 53{t^2} + {t^3} = 8184 - 636t + 12{t^2}$

$\Rightarrow {t^3} - 65{t^2} + 1306t - 7560 = 0$

t=10 satisfies the above equation.

$\Rightarrow {t^2}(t - 10) - 55t(t - 10) + 756(t - 10) = 0$

$\Rightarrow (t - 10)({t^2} - 55t + 756) = 0$

$\Rightarrow (t - 10)(t - 27)(t - 28) = 0$

t has three possible values: 10, 27, 28.

x and y have already been obtained in terms of t. z can also be found in terms of t in the same fashion.

$z(1 + 12 - t) = 30$

$\Rightarrow z = \frac{{30}}{{13 - t}}$

$\left\{ {x,y,z} \right\} \equiv \left\{ {\frac{{12}}{{22 - t}},\frac{{21}}{{31 - t}},\frac{{30}}{{13 - t}}} \right\}$

$\equiv \left\{ {1,1,10} \right\},\left\{ { - \frac{{12}}{5},\frac{{21}}{4}, - \frac{{15}}{7}} \right\},\left\{ { - 2,7, - 2} \right\}$

### $f(x)=x^6+2x^4+x^3+2x+3 $$\mathop {\lim }\limits_{x \to 1} \frac{{{x^n}f(1) - f(x)}}{{x - 1}} = 44$$n=?$

Let $f(x)=x^6+2x^4+x^3+2x+3,x \in R$. Then the natural number n for which $\mathop {\lim }\limits_{x \to 1} \frac{{{x^n}f(1) - f(x)}}{{x - 1}} = 44$ is _ _ _ _ . Solution Since the limit has $\left[ {\frac{0}{0}} \right]$ form, L.H. Rule is applicable. Thus, $\mathop {\lim }\limits_{x \to 1} n{x^{n - 1}}f(1) - f'(x) = 44$ $\therefore nf(1) - f'(1) = 44$ $\therefore n.9 - ({6.1^5} + {8.1^3} + {3.1^2} + 2.1) = 44$ $\Rightarrow 9n - 19 = 44$ $\Rightarrow n=7$